2013
DOI: 10.1136/bcr-2012-008509
|View full text |Cite
|
Sign up to set email alerts
|

Subacute combined degeneration of the spinal cord following recreational nitrous oxide use

Abstract: SUMMARYWe describe a case of a young woman who developed myelopathy and peripheral neuropathy following 1 year of recreational nitrous oxide (N 2 O) use. She presented with uncomfortable tingling sensation in her feet and poor balance. Physical examination revealed mild weakness and hyper-reflexia in the lower limbs. Proprioception and vibration were absent in the lower limbs. Pinprick and light touch sensations were reduced below the sixth thoracic dermatome. A broad-based gait and a positive Romberg sign wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
40
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 15 publications
3
40
0
Order By: Relevance
“…6 When abused chronically and in high volume, nitrous oxide has been associated with myelopathy related to vitamin B 12 deficiency, a disorder in which patients commonly have paresthesia, ataxia, and loss of position and vibration senses. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Other cases have also demonstrated the manifestation of myelopathy from acute nitrous oxide exposure via anesthesia in patients with underlying vitamin B 12 deficiency. [21][22][23][24][25][26] The spinal cord abnormality caused by vitamin B 12 deficiency, often seen on magnetic resonance imaging (MRI) as an irregular demyelination of white matter, is known diagnostically as subacute combined degeneration (SCD).…”
Section: Purposementioning
confidence: 98%
“…6 When abused chronically and in high volume, nitrous oxide has been associated with myelopathy related to vitamin B 12 deficiency, a disorder in which patients commonly have paresthesia, ataxia, and loss of position and vibration senses. [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20] Other cases have also demonstrated the manifestation of myelopathy from acute nitrous oxide exposure via anesthesia in patients with underlying vitamin B 12 deficiency. [21][22][23][24][25][26] The spinal cord abnormality caused by vitamin B 12 deficiency, often seen on magnetic resonance imaging (MRI) as an irregular demyelination of white matter, is known diagnostically as subacute combined degeneration (SCD).…”
Section: Purposementioning
confidence: 98%
“…The finding of a band of thoracic sensory impairment would not be expected with SCD and would be more compatible with TM. A review of the literature identified that both sensory levels and bands of abnormal sensation on the chest have been reported in SCD [3–5]. Although a sensory level might be explained by rare spinothalamic tract involvement [5], there is no satisfactory explanation for the band of abnormal sensation.…”
Section: Discussionmentioning
confidence: 99%
“…Nitrous oxide inhalation, in dentistry or as an abused substance, alters cobalamin (vitamin B12) in an irreversible manner and prevents metabolic utilization, resulting in similar symptoms and imaging findings to subacute combined degeneration. Recreational use of nitrous oxide is becoming more common in adolescents [54]. Copper deficiency can have a similar appearance [55][56][57] and often coexists with vitamin B12 deficiency.…”
Section: Differential Diagnosis: Metabolic and Neurodegenerativementioning
confidence: 99%